2018
DOI: 10.1089/aivt.2017.0030
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting Experimental Strategies for Inhalation Toxicology: The Emergence of Microengineered Breathing-Smoking Human Lung-on-a-Chip

Abstract: Cigarette smoking is major public health problem and a substantial contributor to the pathogenesis of respiratory disorders such as chronic obstructive pulmonary disease and lung cancer. In addition, our society faces the rapidly growing use of tobacco-related products such as electronic cigarettes. Thus, we need reliable model systems that can accurately predict the biological impact of exposure to inhaled smoke and vape and allow recreation of clinically relevant organ-level responses. In this study, we desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…It could also determine the relevant in vivo pharmacokinetic parameters such as mean Lethal Dose (LD50) or half-maximal inhibitory concentration (IC50). [59]…”
Section: Limitations Of Current Breathing Lungs-on-chip and Opportunities Provided By Advancement In Soft-roboticsmentioning
confidence: 99%
“…It could also determine the relevant in vivo pharmacokinetic parameters such as mean Lethal Dose (LD50) or half-maximal inhibitory concentration (IC50). [59]…”
Section: Limitations Of Current Breathing Lungs-on-chip and Opportunities Provided By Advancement In Soft-roboticsmentioning
confidence: 99%
“…For the purpose of identifying the adverse effects of smoke inhalation, the researchers essentially connected the custom-made smoke machine to the LOC microfluidic device. 68 Researchers are further developing a smoking block for a tobacco product, ecigarettes, and e-liquids to investigate smoking-induced abnormal biological responses that happen in the microengineered small areas of different lung regions, particularly designing microalveoli-on-chip format. 62 A very convincing evidence on the tissue affected form such a study was found to be consistent with data from literature.…”
Section: Case Reports Challenges and Opportunities Of Emerging Breath...mentioning
confidence: 99%
“…Tobacco product-induced/associated lung injuries and diseases remain a very important public health concern in both developed and developing countries. For the purpose of identifying the adverse effects of smoke inhalation, the researchers essentially connected the custom-made smoke machine to the LOC microfluidic device . Researchers are further developing a smoking block for a tobacco product, e-cigarettes, and e-liquids to investigate smoking-induced abnormal biological responses that happen in the microengineered small areas of different lung regions, particularly designing microalveoli-on-chip format .…”
Section: Case Reports Challenges and Opportunities Of Emerging Breath...mentioning
confidence: 99%
“…Once established, a dynamic ALI can also be utilized to conduct exposure studies in a more physiologically and clinically relevant context [ 6 ]. Benam et al created a custom smoking machine to replicate biomimetic exposure, however their non-exposed systems remain in a semi-dynamic state [ 59 ].…”
Section: Modeling Lung Biology On-chipmentioning
confidence: 99%
“…In general, co-culture systems are more physiological relevant, as they mimic the complex in vivo microenvironment better than monoculture systems and can be utilized to investigate direct and indirect cell-to-cell interactions that occur between homotypic and heterotypic cell populations. With appropriate cell selection, ALI and shear forces it has been shown that lung-on-a-chip models have the ability to replicate lung barrier function [ 20 , 23 , 26 , 49 , 55 ], lung injury [ 17 , 18 ], inflammation [ 23 , 26 , 49 ], and immune response to cigarette smoke [ 23 , 59 ] and infection [ 23 , 27 , 48 , 55 ].…”
Section: Modeling Lung Biology On-chipmentioning
confidence: 99%